2015
DOI: 10.1186/s13039-015-0188-6
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia-absent radius (TAR) syndrome due to compound inheritance for a 1q21.1 microdeletion and a low-frequency noncoding RBM8A SNP: a new familial case

Abstract: BackgroundThrombocytopenia-absent radius syndrome (TAR; MIM 274000) is a rare autosomal recessive disorder combining specific skeletal abnormalities with a reduced platelet count. TAR syndrome has been associated with the compound inheritance of an interstitial microdeletion in 1q21.1 and a low frequency noncoding RBM8A SNP.ResultsHere, we report on a patient with scapulo-humeral hypoplasia, bilateral radio-ulnar agenesis with intact thumbs, bilateral proximal positioning of the first metacarpal, bilateral fif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 37 publications
0
13
0
4
Order By: Relevance
“…Targeted Sanger sequencing of the 5′ UTR of RBM8A (NM_005105.4; LRG_574t1) detected the known low-frequency SNV c.-21G>A, thereby establishing the molecular diagnosis of TAR syndrome. Compound heterozygosity of the microdeletion and a 5′ UTR SNV is the most common underlying genotype of TAR syndrome [ 3 , 4 , 6 , 12 , 15 , 16 , 17 ]. The parents were unavailable for segregation analysis, but the two variants detected in these siblings conforms to this common genotype, as does their classical presentation of TAR syndrome.…”
Section: Detailed Case Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Targeted Sanger sequencing of the 5′ UTR of RBM8A (NM_005105.4; LRG_574t1) detected the known low-frequency SNV c.-21G>A, thereby establishing the molecular diagnosis of TAR syndrome. Compound heterozygosity of the microdeletion and a 5′ UTR SNV is the most common underlying genotype of TAR syndrome [ 3 , 4 , 6 , 12 , 15 , 16 , 17 ]. The parents were unavailable for segregation analysis, but the two variants detected in these siblings conforms to this common genotype, as does their classical presentation of TAR syndrome.…”
Section: Detailed Case Descriptionmentioning
confidence: 99%
“…The RBM8A gene encodes the RNA-binding motif protein A, also designated the Y14 protein, which is a component of the exon junction complex (EJC), involved in numerous essential cellular functions [ 9 , 10 , 11 ]. Given this housekeeping role of the EJC, RBM8A is widely expressed, including in MGK and osteoblasts [ 9 , 10 , 12 , 13 ]. Functional studies have shown that Y14 levels are significantly lower in the PLTs of TAR syndrome patients, suggesting that here, RBM8A variants decrease protein expression to levels below a critical threshold [ 3 , 9 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All detected CNVs were tested for inheritance by hybridization of the parental DNA with the same array platform. De novo CNVs were confirmed either by FISH analysis or by quantitative real-time PCR as already reported (Vaccari et al, 2014;Tassano et al, 2015). To assess the clinical significance of the detected CNVs, we used several tools.…”
Section: Cnv Detection and Annotationmentioning
confidence: 99%
“…Following the identification of the two SNPs, at least 22 new TAR cases have been reported (Omran et al , ; Bottillo et al , ; Baken et al , ; Idahosa et al , ; Papoulidis et al , ; Reid et al , ; Yassaee et al , ; Al Kaissi et al , ; Kumar et al , ,b; Pereira et al , ; Tassano et al , ; Nicchia et al , ; Jameson‐Lee et al , ). However, the presence of the microdeletion on chromosome 1q21.1 or of the hemizygous SNPs has not been reported in more than half of the described patients (Omran et al , ; Baken et al , ; Idahosa et al , ; Reid et al , ; Al Kaissi et al , ; Kumar et al , ; Pereira et al , ).…”
Section: Diagnosis/differential Diagnosesmentioning
confidence: 99%